2014
DOI: 10.1002/hipo.22303
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discrimination deficits as a function of lag interference in older adults

Abstract: A vital component of episodic memory is the ability to determine the temporal order of remembered events. Although it has been demonstrated that the hippocampus plays a crucial role in this ability, the details of its contributions are not yet fully understood. One proposed contribution of the hippocampus is the reduction of mnemonic interference through pattern separation. Prior studies have used behavioral paradigms designed to assess this function in the temporal domain by evaluating the ability to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…The most common version of the MST utilizes simple, everyday objects on a white background and has been a powerful tool for demonstrating decreases in pattern separation behavior in aging and MCI [10,11,13,15,38]. In addition, several variants of the MST or related tasks designed to test pattern separation performance have shown age-related declines manipulating temporal [39], emotional [40,41], verbal [42], and spatial [43-45] dimensions of lure similarity. In this study, we developed a different manipulation: the use of rich, complex scenes in place of simple objects.…”
Section: Introductionmentioning
confidence: 99%
“…The most common version of the MST utilizes simple, everyday objects on a white background and has been a powerful tool for demonstrating decreases in pattern separation behavior in aging and MCI [10,11,13,15,38]. In addition, several variants of the MST or related tasks designed to test pattern separation performance have shown age-related declines manipulating temporal [39], emotional [40,41], verbal [42], and spatial [43-45] dimensions of lure similarity. In this study, we developed a different manipulation: the use of rich, complex scenes in place of simple objects.…”
Section: Introductionmentioning
confidence: 99%
“…From a cognitive perspective, temporal memory concerns the ability to accurately encode and recall the time and order of past events (DuBrow & Davachi, 2014), whereas, to behaviour analysts, temporal memory effects are typically construed as the effects of time and order of stimulus presentation on subsequent stimulus control. Many studies have established age differences in temporal memory tasks (e.g., Roberts, Ly, Murray, & Yassa, 2014;Rotblatt et al, 2015), but these have, in the main, focused on longer term memory effects.. Within the current cognitive literature, there are four main hypotheses about the basis of reduced temporal memory in older adults.…”
Section: Age-related Variation In Complex Behavioural Tasksmentioning
confidence: 99%
“…Age-related deficits in memory for the temporal order of occurrence of items or events have been well documented in healthy older adults (Blachstein et al, 2012; Kessels et al, 2007; Newman et al, 2001; Old & Naveh-Benjamin, 2008; Roberts et al, 2014; Tolentino et al, 2012; Ulbrich et al, 2009). Recent studies have demonstrated that temporal interference may play a key role in the ability of older adults to remember sequences of stimuli (Roberts et al, 2014; Rotblatt et al, 2015; Tolentino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that temporal interference may play a key role in the ability of older adults to remember sequences of stimuli (Roberts et al, 2014; Rotblatt et al, 2015; Tolentino et al, 2012). Various human and animal studies reviewed by Kesner and Hopkins (2006) have shown that items occurring further apart in a temporal sequence are easier to remember than items that are temporally adjacent.…”
Section: Introductionmentioning
confidence: 99%